Development of a PIC-based wireless sensor node utilizing XBee technology - Yussoff, Ym; Abidin, Husna Zainol; Rahman, Ruhani Ab; Yahaya, Faieza Hanum (2010 2nd IEEE International Conference on Information Management and Engineering, 2010)
This paper presents the performance analysis of Wireless Sensor Network (WSN) used in the high-end applications such as weapons sensor ship, biomedical applications, habitat sensing and seismic monitoring. Recently WSN also focuses on national security applications and consumer applications. This project shall demonstrate the performance of WSN models, which have been developed using PIC. Temperature sensor nodes were deployed in the networks to create sensing phenomena. The results recorded that successful throughput from sensor node, strongly depends on the delay setting. Therefore, the important factors and issues pertaining to the WSN performance will also be determined and describe briefly.